Common Issues Seen in Paediatric Diabetes Clinics, Psychological Formulations, and Related Approaches to Management. (27th February 2018) - Deeb, Asma; Akle, Mariette; Al Ozairi, Abdulla; Cameron, Fergus
Abstract : Diabetes is a chronic disease and its management is associated with multiple challenges. This is particularly the case in children and adolescents. Factors that contribute to difficulties in managing diabetes in youth include psychological characteristics, family dynamics, and social behavior. The purpose of this article is to highlight some psychological issues in children and adolescents with diabetes. We aim to present selected case scenarios encountered by health professionals and to provide tips on strategies for managing psychological aspect of diabetes. We tackle the psychological issues related to diabetes under four main categories: maladaptive disorders, eating disorders, family psychopathology, and family dysfunction. Psychotherapy and psychoanalysis are useful modalities in diabetes management. The psychological intervention is aimed at supporting patients and families to reach a balance between a normal family routine and a good glycemic control. We demonstrate unique requirements in coordinating care for children and adolescents with diabetes and highlight the importance of encouraging a positive behavior. Managing diabetes in children and adolescents needs to be in the form of a collaborative work between health care professionals, children and adolescents, and their families. Caring, supportive family backed up by experienced multidisciplinary team is the best approach to prevent psychological difficulties.